Valid Inequalities for the Green Vehicle Routing Problem - Andrade, Matheus Diógenes; Usberti, Fábio Luiz (Anais do Encontro de Teoria da Computação (ETC); 2020: Anais do V Encontro de Teoria da Computação, 2020)
This work aims to investigate the Green Vehicle Routing Problem (G-VRP), which is an NP-Hard problem that generalizes the Vehicle Routing Problem (VRP) and integrates it with the green logistics. In the G-VRP, electric vehicles with limited autonomy can be recharged at Alternative Fuel Stations (AFSs) to keep visiting customers. This research proposes MILP formulations, valid inequalities, and preprocessing conditions.